1991
DOI: 10.1093/geronj/46.6.m196
|View full text |Cite
|
Sign up to set email alerts
|

Stepping Over Obstacles: Gait Patterns of Healthy Young and Old Adults

Abstract: Falls associated with tripping over an obstacle can be devastating to elderly individuals, yet little is known about the strategies used for stepping over obstacles by either old or young adults. The gait of gender-matched groups of 24 young and 24 old healthy adults (mean ages 22 and 71 years) was studied during a 4 m approach to and while stepping over obstacles of 0, 25, 51, or 152 mm height and in level obstacle-free walking. Optoelectronic cameras and recorders were used to record approach and obstacle cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
285
4
7

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 330 publications
(321 citation statements)
references
References 0 publications
25
285
4
7
Order By: Relevance
“…Previous research has demonstrated that older adults attempt to cross over obstacles in the later part of swing because contact with the obstacle later in swing is less likely to cause a trip in comparison to contact early on in swing due to the relatively more posterior position of the body centre of mass in late swing [4]. The authors noted that, although this strategy resulted in higher toe-clearance the trade-off was reduced heel clearance [4].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous research has demonstrated that older adults attempt to cross over obstacles in the later part of swing because contact with the obstacle later in swing is less likely to cause a trip in comparison to contact early on in swing due to the relatively more posterior position of the body centre of mass in late swing [4]. The authors noted that, although this strategy resulted in higher toe-clearance the trade-off was reduced heel clearance [4].…”
Section: Discussionmentioning
confidence: 99%
“…The authors noted that, although this strategy resulted in higher toe-clearance the trade-off was reduced heel clearance [4]. Other research has highlighted that, when crossing obstacles leading with their prosthesis, unilateral trans-tibial amputees (with no ability to alter prosthetic 'ankle' angle) attend more to how their heel crosses the obstacle compared to able-bodied controls [19].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations